2013
DOI: 10.1002/jbm.a.34752
|View full text |Cite
|
Sign up to set email alerts
|

Better early osteogenesis of electroconductive hydroxyapatite–calcium titanate composites in a rabbit animal model

Abstract: In view of the fact that bone healing can be enhanced due to external electric field application, it is important to assess the influence of the implant conductivity on the bone regeneration in vivo. To address this issue, this study reports the in vivo biocompatibility property of multistage spark plasma sintered hydroxyapatite (HA)-80 wt % calcium titanate (CaTiO3 ) composites and monolithic HA, which have widely different conductivity property (14 orders of magnitude difference). The ability of bone regener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…To develop a bone replacement material, the choice of the second phase depends on the application as well as anticipated functionality. For example, BaTiO 3 , CaTiO 3 , Fe 3 O 4 , and ZnO or Ag can be added to HA as a second phase to introduce the piezoelectric, electrical conductivity, magnetic, and bactericidal properties, respectively . However, brittle nature and the load bearing incapability of the ceramics may limit the broader application of such types of ceramic‐ceramic composites; some examples include HA‐20HA whisker , HA‐20ZrO 2 , and HA‐(Al 2 O 3 coated) ZrO 2 with fracture toughness of 1.4 MPa m 1/2 , 1.5 MPa m 1/2 , and 3 MPa m 1/2 , respectively .…”
Section: Orthopedic Grafting Using Hydroxyapatite‐based Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…To develop a bone replacement material, the choice of the second phase depends on the application as well as anticipated functionality. For example, BaTiO 3 , CaTiO 3 , Fe 3 O 4 , and ZnO or Ag can be added to HA as a second phase to introduce the piezoelectric, electrical conductivity, magnetic, and bactericidal properties, respectively . However, brittle nature and the load bearing incapability of the ceramics may limit the broader application of such types of ceramic‐ceramic composites; some examples include HA‐20HA whisker , HA‐20ZrO 2 , and HA‐(Al 2 O 3 coated) ZrO 2 with fracture toughness of 1.4 MPa m 1/2 , 1.5 MPa m 1/2 , and 3 MPa m 1/2 , respectively .…”
Section: Orthopedic Grafting Using Hydroxyapatite‐based Compositesmentioning
confidence: 99%
“…For example, BaTiO 3 , CaTiO 3 , Fe 3 O 4 , and ZnO or Ag can be added to HA as a second phase to introduce the piezoelectric, electrical conductivity, magnetic, and bactericidal properties, respectively. [69][70][71][72][73] However, brittle nature and the load bearing incapability of the ceramics may limit the broader application of such types of ceramic-ceramic composites; some examples include HA-20HA whisker , HA-20ZrO 2 , and HA-(Al 2 O 3 coated) ZrO 2 with fracture toughness of 1.4 MPa m 1/2 , 1.5 MPa m 1/2 , and 3 MPa m 1/2 , respectively. [74][75][76] Interestingly, a glaring example of HA-based ceramic composite with fracture toughness, higher or equal to that of the cortical bone is still unavailable (see Fig.…”
Section: Orthopedic Grafting Using Hydroxyapatite-based Compositesmentioning
confidence: 99%
“…In recent years, materials with new morphologies have attracted great attention due to their applications in many fields [1][2][3]. Calcium titanate (CT) is a perovskite-type ceramic with outstanding properties that can be used as biomaterials for defect healing and bone regeneration in vivo [4], dielectric resonators in wireless communication systems [5] and high photocatalytic activity of decomposing water [6] in H 2 and O 2 . Despite these applications, most attention has been devoted to the photoluminescence (PL) properties of ceramic materials because of the development of advanced displays for multimedia applications.…”
Section: Introductionmentioning
confidence: 99%
“…Sm 3 þ concentrations were varied in the CT matrix in order to evaluate the maximum photoluminescence intensity and the quenching concentration of this ion, as well as their influence in the structural and morphological behavior. 4 ] was slowly added in 25 mL of deionized water close to the temperature of 0 1C under magnetic stirring (Reaction 1). In a similar way, 0.01 mol of the CaCl 2 Á 2H 2 O was dissolved in 25 mL of deionized water in room temperature, giving rise to a transparent solution.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium titanate (CaTiO 3 ) has gained extensive attention in many biomaterial-related works as a promising bioactive ceramic, primarily due to its higher bone tissue biocompatibility in comparison to pure titanium (Ti) and its alloys, and given its positive surface charge which resembles electrical properties of natural bone 2) . Up to date, several reports proved both, in vitro and in vivo, an augmented and stable biochemical bonding between CaTiO 3 surfaces and bone tissue in addition to an accelerated osseointegration to CaTiO 3 -coated implants [3][4][5][6] . Furthermore, it was shown that aforementioned bone bonding to CaTiO 3 might be increased either through micro-and nanostructuration of CaTiO 3 or by combining this material with carbon in diff erent forms 7,8) .…”
Section: Introductionmentioning
confidence: 99%